Equally supportive but for different reasons: Investigating public support for national energy transition goals vs. their implementation - Yann Blumer; Lukas Braunreiter; Aya Kachi; Rebecca Lordan-Perret; Fintan Oeri (University of Basel, Center of Business and Economics (WWZ), 2018)
Energy system transitions in democracies requires to reconcile national interests and central planning with the public's preferences. To find ways of making public support for national energy strategies and technological implementation more aligned, this article investigates public support for the Swiss national energy strategy and two specific technological measures that are part of it: expansion of hydropower and deep geothermal energy. We address two research questions. First, how does public support for a national energy transition strategy differ from public support for the specific technology endorsed in the energy transition strategy? Second, are there differences in the factors influencing public support for these technologies? We investigate these questions empirically with a survey (n=640) focused on understanding the roles that energy expectations, future orientation, knowledge, and trust play in generating support for these two policy levels and between technologies. We find that while general support for an energy transition is well explained by above factors, this is true only to a much lesser extent for technology support. One conclusions is that while political ideologies play a role for the support of general energy transition goals, the support of energy technologies does not seem to be an issue that is politicized (yet?).
Keywords: 330